Cost management and customer service in business performance: a case study in the garment industry - Perez Nieto, Mariela Aydee; Hernandez-Madrigal, Monica (RAN - Revista Academia & Negocios, 2023)
Purpose: this study aims to examine the existing cost management system within company in the clothing industry. Methodology: through a qualitative and descriptive study, we applied the developing and effective managerial costing model by Lawson et al. (2019). Results: The results reveal the significance of cost management systems and excellent customer service in small businesses to achieve a greater negotiating capacity with customers. Implications: This article contributes with a solid foundation for the diagnosis of a cost management system. Originality: this work offers a comprehensive conceptual framework and practical tools that facilitate professionals to advance in the assessment of cost management systems, thereby influencing decision-making and business performance.